2007
DOI: 10.1038/sj.cdd.4402262
|View full text |Cite
|
Sign up to set email alerts
|

Mutant SOD1 detoxification mechanisms in intact single cells

Abstract: Mutant superoxide dismutase 1 (mtSOD1) causes dominantly inherited amyotrophic lateral sclerosis (ALS). The mechanism for mtSOD1 toxicity remains unknown. Two main hypotheses are the impairment of proteasomal function and chaperone depletion by misfolded mtSOD1. Here, we employed FRET/FLIM and biosensor imaging to quantitatively localize ubiquitination, as well as chaperone binding of mtSOD1, and to assess their effect on proteasomal and protein folding activities. We found large differences in ubiquitination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
(78 reference statements)
0
21
0
Order By: Relevance
“…It is thus possible that SOD1 mutant proteins form different intermediate folding states in vivo depending on the nature of the mutation, and as such may possess different functional interactions with the folding machinery of the cell. Indeed, G85R and G93A proteins were recently shown to have different interactions with HSP70 in cultured cells [41]. On the other hand, the structure and functions of paramyosin, UNC-45, and Ras are diverse (a structural coiled-coil protein, a soluble TPR domain-containing protein and a small GTPase, respectively) and these proteins are not overexpressed as they are expressed from their endogenous chromosomal loci.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus possible that SOD1 mutant proteins form different intermediate folding states in vivo depending on the nature of the mutation, and as such may possess different functional interactions with the folding machinery of the cell. Indeed, G85R and G93A proteins were recently shown to have different interactions with HSP70 in cultured cells [41]. On the other hand, the structure and functions of paramyosin, UNC-45, and Ras are diverse (a structural coiled-coil protein, a soluble TPR domain-containing protein and a small GTPase, respectively) and these proteins are not overexpressed as they are expressed from their endogenous chromosomal loci.…”
Section: Discussionmentioning
confidence: 99%
“…The UPS-mediated degradation of the mutant SOD1 in ALS is realized via the Hsp70-CHIP pathway (Choi et al, 2004;Urushitani et al, 2004;Ishigaki et al, 2007). Experiments showed that only mutant SOD1, but not the wild type protein induces the formation of aggregates during proteasome inhibition (Kabashi and Durham, 2006), as well as only the mutant form seems to be polyubiquitinated in neuronal cells (Basso et al, 2006;Ganesan et al, 2008), mediated by the E3 ligases dorfin, CHIP and NEDL1 (Miyazaki et al, 2004;. These results suggest that even the susceptible motor neurons are capable of degrading mutant SOD1, if the efficiency of the UPS is ensured.…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 98%
“…In cell based assays and mouse models, ALS mutant SOD1G93A and G85R show increased interaction with a number of chaperones, including Hsp70, suggesting that ALS-associated mutant species may result in a depletion of available chaperones and chaperone activity, therefore leading to cellular toxicity (Tummala et al, 2005; Ganesan et al, 2007). Furthermore, reduced levels of the chaperone alpha-B-crystallin (CRYAB) and increased incorporation of other molecular chaperones, including Hsc70, into the insoluble aggregate fraction are features of a faster progressing phenotype in SOD1G93A transgenic mice (Marino et al, 2015).…”
Section: Loss Of Protein Homeostasis In Alsmentioning
confidence: 99%